Rozwój przedsiębiorczości w mikroregionie Dolina Strugu - Mackiewicz, Jan; Zadworny, Waldemar (Entrepreneurship Development in the Micro-Region of Strug, 2006)
The Velly of Strug is a case of the Mikroregion where followed a dynamic economic and social development through the activity of chief officers of a group of villages and mayors, first of all their participation in EU programms. This process is an evidence for innovation and pro-enviromental activities aimed to the local community and bring doubtless calculable profits.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 523-530